Nursing Students' Attitudes towards Seeking Psychological Professional Help - Gomaa, Salma Mohammed; Abdel Azeem, Fatma Mansour (International Journal of Innovative Research in Medical Science, 2018)
Psychological help-seeking means to benefit different sources of support system for the difficulties people have. The aim of this study was to investigate nursing students' attitudes towards seeking psychological help. Methods: A cross-sectional Study institutional based was used, using a standardized instrument Attitudes toward Seeking Professional Psychological Help Scale. Subjects: The study included all available nursing student at the time of data collection (n=50) in Hafr Al-Batin university. Results: Obtained data were evaluated with variance analysis 50 undergraduate students overall response, The majority 80 % showed positive attitude, while 20 % showed negative attitude toward Psychological Help .The implications of the findings of this study were discussed and suggestions for future research were made.